Completeness and Coherence of Kafka’s Worlds - Fořt, Bohumil (Bohemistyka, 2025)
The study offers a novel perspective on Franz Kafka’s novels The Trial and The Castle. Unlike other analyses that emphasize the supernatural power of the court and the castle as embodied in dehumanized bureaucratic structures, this study highlights the role of the subjects in shaping and functioning within these structures. Methodologically, it examines the phenomena of missing or distorted information and analyzes how these types of information contribute to the specific semantic construction of the novels, resulting in their (in)completeness and (in)coherence.